PELAKSANAAN PENYIDIKAN TERHADAP ANAK YANG TERLIBAT DALAM TRANSAKSI NARKOTIKA - Ana Ramadhona (STIH Putri Maharaja, 2020)
One crime that often occurs in Indonesia is drug use. Protection of children in a national society is a benchmark of the nation's civilization, so it must be pursued in accordance with the abilities of the nation. The study was conducted by using an empirical juridical approach. The data used are primary data obtained by interview and secondary data obtained through literature studies. The results of the study are described as follows: As for the implementation of investigations against children involved in narcotics transactions in the jurisdiction of Payakumbuh Police conducted by investigators basically in accordance with the Criminal Procedural Code and Law Number 11 Year 2012 Concerning the Criminal Justice System that applies even though in its implementation it has not maximize due to some limitations. The rights granted to child as suspects are also given in the form of rights avoided from acts of violence, accompanied by legal counsel and social guidance, the right to express opinions, views freely, receive care and welfare, and the right to be treated equally, Obstacles arising in investigations of children involved in Narcotics transactions in the Payakumbuh Police jurisdiction, including the time to detain children is very limited, namely seven days and can be extended eight days so that investigators must be extra fast to be able to complete the case file, should conduct an examination at the BPOM Padang laboratory. It must be also delivered and picked up by investigators and wait for the results of BAPAS research on the child concerned, and the absence of special investigators for children.